Estimating prevalence and incidence of sexually transmitted infections among South African Women: implications of combined impacts of risk factors - Wand, Handan (Int J STD AIDS, 2020)
In addition to being the epicentre of the HIV epidemic, South Africa also has the highest burden of sexually transmitted infections (STIs) in the world. Therefore, understanding the most influential risk factors of STIs is a research priority. Using the data from 9,948 women who resided in KwaZulu Natal, South Africa, we estimated the population attributable risk to quantify the combined impacts of the most influential factors on STI diagnosis. Overal STI Prevalence was 20%, and STI incidence was 15 per 100 person-year. Four factors, age at sexual debut, single/not cohabiting, two or more sex partners and parity<3 were identified as the most influential risk factors for STI prevalence and incidence rates. However, these factors collectively associated with only 51% and 53% of the excess STI prevalence and incidence rates, respectively. These relatively modest impacts provide empirical evidence for the significant impacts of unmeasured factors on STIs. Culturally and socially appropriate prevention programs may be more effective to target those at highest risk of STIs.